Thermogenic effect of an acute ingestion of a weight loss supplement - Hoffman, J.; Kang, J.; Ratamess, N.; Rashti, S.; Tranchina, C.; Faigenbaum, A. (Journal of the International Society of Sports Nutrition, 2009)
The purpose of this study was to examine the acute effects of a weight loss supplement on resting oxygen uptake (VO2), respiratory quotient (RQ), caloric expenditure (kcal), heart rate (HR), and blood pressure (BP) in healthy and physically active individuals.